If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (1 + u)(5u + -6) = 0 Reorder the terms: (1 + u)(-6 + 5u) = 0 Multiply (1 + u) * (-6 + 5u) (1(-6 + 5u) + u(-6 + 5u)) = 0 ((-6 * 1 + 5u * 1) + u(-6 + 5u)) = 0 ((-6 + 5u) + u(-6 + 5u)) = 0 (-6 + 5u + (-6 * u + 5u * u)) = 0 (-6 + 5u + (-6u + 5u2)) = 0 Combine like terms: 5u + -6u = -1u (-6 + -1u + 5u2) = 0 Solving -6 + -1u + 5u2 = 0 Solving for variable 'u'. Factor a trinomial. (-1 + -1u)(6 + -5u) = 0Subproblem 1
Set the factor '(-1 + -1u)' equal to zero and attempt to solve: Simplifying -1 + -1u = 0 Solving -1 + -1u = 0 Move all terms containing u to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + -1u = 0 + 1 Combine like terms: -1 + 1 = 0 0 + -1u = 0 + 1 -1u = 0 + 1 Combine like terms: 0 + 1 = 1 -1u = 1 Divide each side by '-1'. u = -1 Simplifying u = -1Subproblem 2
Set the factor '(6 + -5u)' equal to zero and attempt to solve: Simplifying 6 + -5u = 0 Solving 6 + -5u = 0 Move all terms containing u to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + -5u = 0 + -6 Combine like terms: 6 + -6 = 0 0 + -5u = 0 + -6 -5u = 0 + -6 Combine like terms: 0 + -6 = -6 -5u = -6 Divide each side by '-5'. u = 1.2 Simplifying u = 1.2Solution
u = {-1, 1.2}
| 12-6y-1= | | f(x)=(1.5)x | | 1.25(2c-1)=3c-2 | | 3b+1=28 | | 0.06(a+200)+0.01a=172 | | x/9-9=8 | | 3(x+5)+4(x-3)+-6x=4 | | (8x^2-7x+2)+(3x^2-9x-6)= | | 2(x-4)+x-y=2y-9 | | -8(x-7)-9=47 | | 2(s+6)+2(s-1)+-4=74 | | (5z-9)(8+z)=0 | | x/3=4x/21-7 | | 60x-50=15x-5 | | x/3=4x/21 | | 13-4y+1y= | | 3(m+3)+5(m+1)+-6m=50 | | m=40 | | 6x+3(-3x-7)=0 | | 5x+15=x-20 | | 9xsquared-21=0 | | X-6-x-4=10-c | | -104=5x-3(5x+8) | | .5f=c+6u | | -3+5(b+4)+4(b+3)=2 | | x^(-3/5)=27 | | -7x-6(2x+5)=84 | | 3(n+3)+-2n+2(n+4)=65 | | 8-5x=2c-9x | | 16l=4c^2+9 | | -x/6=5-8 | | 12(t+2)+-7t+-8=6 |